The Cross-Selectivity in Palladium-Catalyzed Coupling of Simple Aryl C–H Bonds - Lu, Wenjun (Synlett, 2024)
Pd-catalyzed cross-couplings of C–H bonds have been pursued by researchers to produce unsymmetrical C–C bonds directly for over 50 years. Such bonds are currently prepared by Suzuki, Kumada, Stille, Neigishi, Heck, or Sonogashira coupling of C–halogen with C–M or C–H bonds. A big challenge is to obtain high cross-selectivity of cross-coupling products, especially when the substrates have similar chemical C–H bonds, such as simple arenes. Lu and co-workers have studied Pd catalysis in the cross-couplings of aryl C–H bonds since 2003. This account introduces their strategy, understanding, and research in cross-selectivity control, C–H activation modes, and cross-coupling establishment, and discusses the applications of the approach in synthesis.1 Introduction2 Cross-Selectivity Control3 Conclusion
Keywords: palladium; arene; C–H activation; cross-coupling; selectivity